Histone deacetylase 4 and 5 translocation elicited by microsecond pulsed electric field exposure is mediated by kinase activity - Safaei, Zahra; Thompson, Gary L. (Frontiers in Bioengineering and Biotechnology, 2022)
Electroporation-based technologies using microsecond pulsed electric field (µsPEF) exposures are established as laboratory and clinical tools that permeabilize cell membranes. We demonstrate a µsPEF bioeffect on nucleocytoplasmic import and export of enzymes that regulate genetic expression, histone deacetylases (HDAC) -4 and -5. Their µsPEF-induced nucleocytoplasmic transport depends on presence and absence of extracellular calcium ions (Ca2+) for both MCF7 and CHO-K1 cells. Exposure to 1, 10, 30 and 50 consecutive square wave pulses at 1 Hz and of 100 µs duration with 1.45 kV/cm magnitude leads to translocation of endogenous HDAC4 and HDAC5. We posit that by eliciting a rise in intracellular Ca2+ concentration, a signaling pathway involving kinases, such as Ca2+/CaM-dependent protein kinase II (CaMKII), is activated. This cascade causes nuclear export and import of HDAC4 and HDAC5. The potential of µsPEF exposures to control nucleocytoplasmic transport unlocks future opportunities in epigenetic modification.